Aerobic bacteriology of Chronic Suppurative Otitis Media (CSOM) in a tertiary care hospital: A retrospective study - Sanjana, RK; Singh, YI; Reddy, NS (Journal of College of Medical Sciences-Nepal, 2012)
The present study was carried out to determine the aerobic microorganisms involved and their antibiotic sensitivity pattern in patients with Chronic Suppurative Otitis Media (CSOM) and to provide a guideline for empirical antibiotic therapy. Between March 2009 to February 2011, the ear discharge samples submitted at the microbiology laboratory were processed aerobically and all the isolates were included in this study. All organisms were identified morphologically and biochemically by standard laboratory procedures and antibiotic susceptibility pattern was determined by modified Kirby Bauer disc diffusion method as per National Committee for Clinical Laboratory Standard recommendations. Out of a total of 214 samples, microbiological culture was yielded from 202 (94.3%) specimens. Single organism were isolated from 168 (78.5%) of the culture positive specimens, while the remaining 34 (15.9%) had two or more organisms isolated. Pseudomonas aeruginosa 59 (35.1%) was the most common isolate, followed by Staphylococcus aureus 42 (25.0%) including 5 (3%) of the Methicillin Resistant Staphylococcus Aureus (MRSA). Antibiotic sensitivities of Pseudomonas aeruginosa showed that 93.2% isolates were sensitive to tobramycin, whereas, 91.5% isolates were sensitive to ceftazidime and 77.9% to amikacin.Only 50.8% of the isolates of Pseudomonas aeruginosa were sensitive to ciprofloxacin and 25.4% to gentamicin. For Staphylococcus aureus (other than MRSA) 95.2% were sensitive to cloxacillin, 83.3% to gentamicin and 78.5% to erythromycin. Only 07.1% were sensitive to ampicillin and 26.1% to ciprofloxacin. Pseudomonas aeruginosa was the most common isolate followed by Staphylococcus aureus. More than 90% of Pseudomonas and 90% of Staph aureus were sensitive to tobramycin and cloxacillin respectively. Therefore, these two drugs may be included in the formulary to cover the most common aerobic isolates involved in CSOM. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 1-8 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6673